2011
DOI: 10.1007/s00125-011-2059-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes on endothelial cell response during sepsis

Abstract: Aims/hypothesis Several endothelial pathways of cell adhesion, coagulation and vascular endothelial growth factor (VEGF) signalling are activated during sepsis. The objective of this analysis was to investigate the influence of diabetes on biomarkers of endothelial cell activation in sepsis. Methods This was a prospective observational cohort study of a convenience sample of adult patients (age ≥18 years) for whom infection was clinically suspected and who presented to an urban tertiary care emergency departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
(59 reference statements)
1
19
0
7
Order By: Relevance
“…Coagulation and endothelial dysfunction have been implicated in sepsis pathophysiology [18]. Sepsis outcomes are worse in obese patients as well as those with diabetes [19,20,21]. Cardiovascular disease compromises the host response to sepsis and septic shock, pointing to connections between cardiovascular and infection risk in this population [22].…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation and endothelial dysfunction have been implicated in sepsis pathophysiology [18]. Sepsis outcomes are worse in obese patients as well as those with diabetes [19,20,21]. Cardiovascular disease compromises the host response to sepsis and septic shock, pointing to connections between cardiovascular and infection risk in this population [22].…”
Section: Discussionmentioning
confidence: 99%
“…The major implication is that for a given stressor, the responses in males and females, and the resulting pathology should the stressor not be removed, are likely to differ. Multiple comorbidities such as diabetes, hypertension, and heart failure, which have already been shown to display sex differences with respect to onset, frequency, morbidity, and mortality, also impact microvascular function [4, 11, 13, 84, 93, 107]. …”
Section: Conclusion and Missing Information (Eg Future Studies Armentioning
confidence: 99%
“…Endothelial activation has been implicated in the pathogenesis of sepsis [53] and diabetes is itself known to activate endothelium. A recent study of 207 sepsis patients (of whom 30% had diabetes) showed that markers of endothelial cell activation (plasma E-selectin and soluble fms-like tyrosine kinase-1 [sFLT-1]) were higher in diabetes [54]. …”
Section: Diabetes and The Immune Systemmentioning
confidence: 99%